Generalized Epilepsy Syndromes of Adolescence - Samanta, Debopam; Willis, Erin (Journal of Pediatric Epilepsy, 2015)
“Idiopathic” generalized epilepsies (juvenile absence epilepsy, juvenile myoclonic epilepsy, and epilepsy with generalized tonic–clonic seizures alone) are the most frequent group of epilepsies with onset during adolescence and constitute 15 to 20% of all epilepsies. These syndromes have overlapping clinical features and genetic origins as well as similar electroencephalographic findings. There are primarily three seizure types that occur with these epilepsy syndromes: generalized tonic–clonic, absence, and myoclonic seizures. Standard neurologic examination and neuroimaging studies do not generally reveal any abnormality. Potential precipitating factors are many, including sleep deprivation, fatigue, alcohol use, photic stimulation, and menstruation. The characteristic electroencephalographic abnormality consists of diffuse, bilateral, symmetric, and synchronous 4 to 6 Hz polyspike and wave complexes. Idiopathic generalized epilepsies are generally associated with low mortality and typically respond well to treatment. The most effective antiepileptic drug for these disorders is sodium valproate, but it should be used with caution in adolescent females who are of childbearing age. Levetiracetam, lamotrigine, topiramate, and zonisamide can also be used as effective monotherapy. Carbamazepine, oxcarbamazepine, phenytoin, gabapentin, and vigabatrin may exacerbate myoclonic and absence seizures in juvenile myoclonic epilepsy.
Keywords: idiopathic generalized epilepsy; juvenile myoclonic epilepsy; juvenile absence epilepsy; generalized tonic–clonic seizures